2022
DOI: 10.1371/journal.pone.0269414
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cardiovascular and renal outcomes between dapagliflozin and empagliflozin in patients with type 2 diabetes without prior cardiovascular or renal disease

Abstract: Background Cardiovascular and renal benefits of sodium glucose co-transporter 2 inhibitors (SGLT2i) have been clearly demonstrated. However, studies comparing the effects of dapagliflozin and empagliflozin are scarce. In addition, relatively few studies have analyzed the effects of SGLT2i in diabetic patients without established atherosclerotic cardiovascular disease (ASCVD), chronic kidney disease (CKD), or heart failure (HF), and current guidelines recommend SGLT2i and other antidiabetic drugs equally in thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The results from this presented study were in agreement with several studies, which found no significant differences in cardiovascular outcomes between dapagliflozin and empagliflozin. 17 , 18 , 19 , 20 These findings suggested a class of SGLT2 inhibitors in managing cardiovascular risks in DM patients, irrespective of the specific SGLT2 inhibitors used. However, contrasting outcomes have been observed in some studies.…”
Section: Discussionmentioning
confidence: 94%
“…The results from this presented study were in agreement with several studies, which found no significant differences in cardiovascular outcomes between dapagliflozin and empagliflozin. 17 , 18 , 19 , 20 These findings suggested a class of SGLT2 inhibitors in managing cardiovascular risks in DM patients, irrespective of the specific SGLT2 inhibitors used. However, contrasting outcomes have been observed in some studies.…”
Section: Discussionmentioning
confidence: 94%
“…Among all trails included, the heaviest weight of the statistical analysis depended on EMPEROR-preserved, where empagliflozin proved to be more effective in reducing the risk of exacerbation of HF than dapagliflozin [ 53 ]. Furthermore, the empagliflozin group had more significant beneficial effects on high-density lipoprotein (HDL) and low-density lipoprotein (LDL) and lower glycated hemoglobin levels than dapagliflozin [ 54 , 55 ]. Interestingly, we found that empagliflozin present an effective role in reducing the risk of AF after removing EMPEROR-preserved in the sensitivity analysis.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Kedua kelompok juga terbukti menurunkan angka kejadian kematian kardiovaskular, tekanan darah, gagal jantung, ataupun kematian karena semua sebab; penurunan kematian kardiovaskular dan tekanan darah lebih signifikan pada kelompok empagli ozin, sedangkan penurunan risiko hospitalisasi gagal jantung lebih signifikan pada kelompok dapagli ozin. 15,[19][20][21][22][23] Yang, et al, menyatakan fungsi ginjal pada kelompok empagli ozin menunjukkan tren penurunan fungsi, sedangkan pada kelompok dapagli ozin menunjukkan tren perbaikan fungsi. Walau tidak sebaik dapagli ozin, empagli ozin tetap menurunkan risiko gagal ginjal lebih baik bila dibandingkan plasebo.…”
Section: Empagli Ozinunclassified
“…Walau tidak sebaik dapagli ozin, empagli ozin tetap menurunkan risiko gagal ginjal lebih baik bila dibandingkan plasebo. 17,21 Manfaat dapagli ozin dan empagli ozin pada pasien DM tipe 2 juga dapat dilihat pada penelitian DECLARE-TIMI 58 dan EMPA-REG. Penelitian DECLARE-TIMI 58 bertujuan untuk mengevaluasi dampak kardiovaskular dan ginjal dapagli ozin versus plasebo pada 17.160 pasien DM tipe 2 yang memiliki atau berisiko ASCVD.…”
Section: Empagli Ozinunclassified